O erotismo revisitado na poética de Herberto Helder - FERNANDEZ, Rafaella Diaz (Universidade Federal do Pará, 2017)
The Herberto Helder’s writings are very extensive and include works of poetry and translation. It is noticeable in his way of writing a close relationship between them. Both emerge displaying an erotic potence which plays a fundamental role in the Herbert’s creation. The translation is intrinsically related to creation, the peculiar manner the poet names this work poems changed to Portuguese” itself, reveals it. Poetry and translation also promote violence against the language, both of them deform it, moving it from a place of meaning to another applying the power of the empty on it. The word meaning deconstruction is what makes poetic creation possible. The Herbert’s writing is related to the body and sexual organs images, blood, sperm and spittle aim at the deconstructed body now thought in energetic parts, and it is from the deformation that emerges the whole for the poetic act. It is intended to think about the importance of eroticism as a vector of poetic construction. In this respect, the Georges Bataille’s reflections are fundamental to guide the eroticism and relate it to the Herberto Helder’s writings. In this way, the hypotheses launched here is that eroticism imposes a violence against the word and the body which is necessary for the work of creation. In this sense, our seek is for the presence of eroticism in the poetry and translation of Herberto Helder, privileging the texts where the image of the creation are found.